PENGARUH LINGKUNGAN KERJA, STRES KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PT. FORISA NUSAPERSADA LAMONGAN - Miftahul Huda; Moh. Azus Shony Azar (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2021)
This study aims to determine the Work environment, work stress and workload on the performance of PT. Forisa Nusapersada Lamongan employees. The hypothesis proposed in this study are: a). Work environment influences the performance of PT Forisa Nusapersada Lamongan employees. b). Job stress affects the performance of PT Forisa Nusapersada Lamongan employees. c). Workload affects the performance of PT Forisa Nusapersada Lamongan employees.The population in this study were all employees who were in PT Forisa Nusapersada Lamongan as many as 97 people. The sample used was 97 respondents. The sampling technique used in this study was to use the "saturated sampling" method. Saturated sampling method is a sample determination technique if all members of the population are used as samples. Data was obtained through primary data by distributing questionnaires to be responded to and secondary data through some data obtained from PT Forisa Nusapersada Lamongan.The statistical method used is the Data Quality Test (Test Validity and Reliability), Multiple Linear Regression Analysis, Classic Assumption Test (Normality Test, Multicollonierity Test, Heteroscedasticity Test and Autocorrelation Test), Model Feasibility Test (F Test and Detremination Coefficient Test) and Testing Hypothesis (t test).The test results show that both partially and simultaneously, Work environment variabels have a significant effect on employee performance, work stress variabels have a significant effect on employee performance and workload variabels have a significant effect on employee performance